Reform of agricultural land property rights system and grain production resilience: Empirical evidence based on China’s “Three Rights Separation” reform - Zeng Wei; Jiquan Peng; Yan Zhao; Xijian Li; Cheng Wang (PLoS ONE, 2025)
The latest reform in China’s agricultural land rights system has implemented the “Three Rights Separation” reform, distinguishing between ownership rights, contract rights, and management rights of rural land. This reform is a significant step taken by the Chinese government to ensure a rational allocation of agricultural land resources, contributing greatly to enhancing food production resilience and promoting food security. This paper analyzes panel data from 30 Chinese provinces from 2005 to 2021 to assess the resilience levels in grain production. It utilizes a multi-period Difference-in-Differences model to examine the effects of the separation of three rights of agricultural land on this resilience, including their mechanisms of action. The findings reveal that(1)although the resilience of grain production in China has progressively improved over the study period, it remains low, indicating substantial potential for enhancement;(2)The separation of three rights of agricultural land significantly boosts the resilience of grain production, a conclusion corroborated by robustness tests;(3)The analysis shows that the policy promotes resilience by facilitating land transfer and boosting investments in agricultural productivity;(4)Heterogeneity analysis indicates that the policy’s impact is more pronounced in major grain-producing areas and central regions, with stronger effects observed in northern wheat-growing areas compared to southern rice-growing regions.